2022
DOI: 10.36004/nier.es.2022.1-08
|View full text |Cite
|
Sign up to set email alerts
|

Gender Profile of Income and Consumption: Evidence From the National Transfer Accounts of Moldova

Abstract: The use of the National Transfer Accounts (NTA) methodology has opened up the possibility of examining gender differences in income and consumption throughout the life cycle. This article presents the results of the study of the gender profile of income and consumption based on the NTA of Moldova for 2019. Moldova is characterized by a low level of employment of the population, low incomes and a high involvement of the population in international labor migration. Women's labor incomes are lower than men's thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
6
0
1
Order By: Relevance
“…Self-perceived health status has been taken as the dependent variable in the study. Although a study indicated that elderly Indians tend to report more positive perception of health than that indicated by objective measures (Cramm et al ., 2015), many suggest that although there are many factors like life and work pressure, spiritual status, interpersonal relations, level of education, material welfare and presence of behavioural vices which influence self-rated health, it is still a good reflector of objective health status (Wu et al ., 2013; Gagauz et al ., 2017). Self-rated health captures illness in a more inclusive manner, even the diseases yet to be diagnosed but present in a preclinical stage, and is also thought to be a dynamic evaluation of health, not only the current state of health, and a good predictor of mortality as well (Idler and Benyamini, 1997; Menec et al ., 1999; Rahman and Barsky, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Self-perceived health status has been taken as the dependent variable in the study. Although a study indicated that elderly Indians tend to report more positive perception of health than that indicated by objective measures (Cramm et al ., 2015), many suggest that although there are many factors like life and work pressure, spiritual status, interpersonal relations, level of education, material welfare and presence of behavioural vices which influence self-rated health, it is still a good reflector of objective health status (Wu et al ., 2013; Gagauz et al ., 2017). Self-rated health captures illness in a more inclusive manner, even the diseases yet to be diagnosed but present in a preclinical stage, and is also thought to be a dynamic evaluation of health, not only the current state of health, and a good predictor of mortality as well (Idler and Benyamini, 1997; Menec et al ., 1999; Rahman and Barsky, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of India, by 2030 almost half of the disease burden will be borne by elderly people with high levels of non-communicable diseases, smoking habits and physical inactivity (Chatterji et al ., 2008; Munsur et al ., 2010). The regional case studies in India and other countries also reflect that the prevalence of unhealthy lifestyles is associated with morbidity among elderly people (Simsek et al ., 2014; Machón et al ., 2016; Gagauz et al ., 2017; Kaur et al ., 2017). Also there occurred a steady deterioration in self-perceived health status among Indian elderly people over the recent decades, even after controlling for socio-economic characteristics (Husain and Ghosh, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations